(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
IL-6 levels are significantly elevated in COVID-19 patients and are associated with poor clinical outcomes. Inhibiting IL-6 is thought to be a unique therapeutic strategy for the control of dysregulated host responses in SARS-CoV-2. The present study focuses on evaluating the research productivity of IL-6 level in SARS-CoV-2 infection using various bibliometric indicators and analysed 4510 research papers related to IL-6 levels in SARS-CoV-2 from the Scopus database and VOSViewer© tool applied for visualization. The results revealed that ascendant trends in the publications and USA, China and Italy have secured top three position in numbers of publications. Study observed that “Dagna L.” received top prolific author rank. Article entitled “Clinical features of patients infected with 2019 novel coronavirus in Wuhan, China” received maximum of 15364 total citations, whereas “Frontiers in Immunology” and “Journal of Medical Virology” secured in top two highly productive journals in the subject with extreme link strength. With regard to organisation, “Tongji Medical College-China” reported highly dynamic organization. “Covid-19”; “SARS-Cov-2”; “Interleukin” received maximum occurrences with high link strength. In view of global mounting public health issue of COVID-19, primarily due to increased viral transmissibility and associated cytokine storm, the present study will helpful for the medical professionals to know the research trends and also library authority for updating collection development policy in the specific subject domains.